Ensaio de inseticidas no combate a insetos filófagos do cacaueiro, no Espíritu Santo - Smith F., Enrique; Abreu, J.M.; Ventocilla, J.A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Colaspis ornata Germ., Colaspis spp., Nodonota sp., Lordops sp., Naupactus sp., and Lasiopus cilipes Shal, are the insects mainly responsible for damage to cacao leaves in Linhares, Espíritu Santo. The efficacy of dusting with chlorinated insecticides (BHC 1 percent, BHC 1.5 percent and Endrin 2 percent) and phosphorous compounds (Malathion 4 percent, Parathion 2 percent and Diazinon 1.5 percent) to control phyllophagous insects has been investigated. Trials were made on yielding trees during the flushing season and the effects on two groups of pests and one specie/index for each group, observed. Chlorinated insecticides were more efficient than the posphorous compounds. BHC 1.5 percent gave better control of both leaf-beetles and weevils, whereas BHC 1 percent showed low efficacy, compared to the phosphorous compounds, in the control of these insect pests.